Natural History of the Lutz's Frog Cycloramphus lutzorum Heyer, 1983 (Anura: Cycloramphidae) in the Brazilian Atlantic Forest: Description of the Advertisement Call, Tadpole, and Karyotype - Lima, Andre M. X.; Garey, Michel V. [UNESP]; Noleto, Rafael B.; Verdade, Vanessa K. (Soc Study Amphibians Reptiles, 2010)
We describe the advertisement call, tadpole, karyotype, and additional information on the natural history of Cycloramphus lutzorum from southern Brazil. Sonograms were generated from digitally recorded calls. Tadpoles were collected in the field for description in the lab, and an adult was collected for karyotyping. Data on seasonal activity were gathered monthly from November 2005 to November 2007. All tadpoles (N = 21), juveniles (N = 18), and adults (N = 52) were found exclusively in streams. Reproduction, as identified by calling frogs, occurred from July through November. Frogs call all day long, but mostly at dusk, from rock crevices inside the stream edges near the splash zone. The call is short and loud, with 11 pulsed notes, of 491-641 ms, with a dominant frequency of 0.98-1.39 kHz. We describe the exotrophic and semiterrestrial tadpoles, always found in constantly humid vertical rock walls in the stream. Tadpoles of C. lutzorum are recognized by differences in labial tooth row formula, eye diameter, body shape, position of nares, and development of tail. Like congeneric species, the karyotype of C. lutzorum comprises 26 metacentric and submetacentric chromosomes. Cycloramphus lutzorum is restricted to and adapted for living in fast flowing streams, many of which are threatened by deforestation, pollution, and habitat loss. Therefore, we recommend the status of C. lutzorum be changed from its current "Data Deficient" to "Near Threatened (NT)" in the IUCN species red list.